2009
DOI: 10.2202/1542-0485.1269
|View full text |Cite
|
Sign up to set email alerts
|

Organic Food Consumption Patterns

Abstract: This research addresses two important issues for the future expansion of organic consumption in France. The first one is related to knowing whether the organic choice is a permanent feature of consumer's attitude or not: Do organic buyers occasionally pick one organic product or do they choose organic for "several" categories? The second issue concerns the impact of prices on buying organics which is revisited, distinguishing between capturing new consumers and increasing the demand coming from people already … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
42
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 1 publication
7
42
1
4
Order By: Relevance
“…However, Monier et al () conclude that organic price changes do not affect the general decision to buy organic, which is observed across several categories, probably because organic price changes are marginal compared with the price gap of organic versus conventional food. Moreover, evidence shows that price sensitivity differs between product categories.…”
Section: Results and Conclusion Per Research Questionmentioning
confidence: 99%
“…However, Monier et al () conclude that organic price changes do not affect the general decision to buy organic, which is observed across several categories, probably because organic price changes are marginal compared with the price gap of organic versus conventional food. Moreover, evidence shows that price sensitivity differs between product categories.…”
Section: Results and Conclusion Per Research Questionmentioning
confidence: 99%
“…For example, Blend and Van Ravenswaay (1999) find that higher levels of education increase the probability that a consumer would purchase eco-labeled apples. Several others find that education is associated with a higher probability of purchasing organics (Bellows et al, 2008;Monier et al, 2009;Zepeda and Li, 2007). Some studies have found that higher education levels are correlated with water saving behaviors (Berk et al, 1993;Gilg and Barr).…”
Section: Previous Literaturementioning
confidence: 99%
“…Experimental studies showed, for example, that the manipulation of pricing strategies can result in lower consumption of unhealthy food products and raise the demand for healthy ones (French et al ., 1997; French, 2003). The high cost of organic food has been identified as a factor inhibiting consumer decision in favour of organic products (Magnusson et al ., 2001; Zanoli and Naspetti, 2002; Shepherd et al ., 2005; Hughner et al ., 2007; Monier et al ., 2009). This is an especially salient argument in light of the economic financial crisis that started in 2008.…”
Section: Conceptual and Empirical Backgroundmentioning
confidence: 99%